Korean children's preference formation based on social categories: comparison between gender cues and age cues. Issue 2 (3rd March 2020) - Kim, Jahee; Kim, Geunyoung
ABSTRACT: Previous studies have indicated that young children are particularly sensitive to gender information when making social judgments. The present study was designed to examine Korean children's choice of either same-gender information or same-age information when they saw unfamiliar objects. All 78 participating children's native language was Korean, which is less gendered and more age-oriented than most Western languages. Children demonstrated preferences for unusual objects endorsed by individuals of the same gender as theirs but did not show a similar preference when the objects were endorsed by children of the same age as theirs. When they had to choose between same-gender information and same-age information, children tended to select the same-gender alternative. This suggests that gender may be a more robust social cue used by young children than age when making social judgments, regardless of their linguistic culture. Implications concerning the hierarchies of social categories were discussed.